Cobalt ferrite hollow spheres: synthesis by hydrothermal method and application as catalyst - Kim Thư, Phan Thị; Hòa, Le Thi (Hue University Journal of Science: Natural Science, 2020)
This paper describes the in situ synthesis of cobalt ferrite (CoFe2O4) using carbonaceous microspheres prepared from a glucose solution as a template, followed by subsequent heat treatment. The obtained material was characterized using energy-dispersive X-ray spectroscopy (EDX), scanning electrode microscope (SEM), vibrating sample magnetometer (VSM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), nitrogen adsorption/desorption isotherms, and ultraviolet-visible spectroscopy (UV–Vis). The calcination of the precursor provides cobalt ferrite hollow spheres sized 300–400 nm with magnetic saturation of 59 eV. CoFe2O4 was used as a catalyst for rhodamine-B photocatalytic decomposition under visible light. The kinetics of rhodamine-B decomposition is also addressed.